Advances in Finance & Applied Economics (Springer Singapore, 2018)
Discussing a wide range of topics of contemporary relevance from the domain of finance and economics, this book presents a collection of twenty-four research papers, which were selected on the basis of their topicality, the novelty of their methods, and the importance of their subject matter. All papers pursue an empirical approach to address key research issues, and are categorized into three major parts. Part one includes papers related to development economics and environmental economics. The second part focuses on monetary economics, public economics, and behavioral economics, while the third tackles issues concerning corporate finance and financial risk management. Bringing together works of scholars from around the world, the book presents a truly global perspective, and not only serves as an essential guide on the topic for researchers, but also has a distinctive role to play in policymaking. .